Quiet is the New Loud: Pausing and Focus in Child and Adult Dutch. (March 2015) - Romøren, Anna Sara H; Chen, Aoju
In a number of languages, prosody is used to highlight new information (or focus). In Dutch, focus is marked by accentuation, whereby focal constituents are accented and post-focal constituents are de-accented. Even if pausing is not traditionally seen as a cue to focus in Dutch, several previous studies have pointed to a possible relationship between pausing and information structure. Considering that Dutch-speaking 4 to 5 year olds are not yet completely proficient in using accentuation for focus and that children generally pause more than adults, we asked whether pausing might be an available parameter for children to manipulate for focus. Sentences with varying focus structure were elicited from 10 Dutch-speaking 4 to 5 year olds and 9 Dutch-speaking adults by means of a picture-matching game. Comparing pause durations before focal and non-focal targets showed pre-target pauses to be significantly longer when the targets were focal than when they were not. Notably, the use of pausing was more robust in the children than in the adults, suggesting that children exploit pausing to mark focus more generally than adults do, at a stage where their mastery of the canonical cues to focus is still developing.